Important times for breastfeeding support: a qualitative study of mothers' experiences. Issue 2 (3rd March 2020) - Fraser, Melanie; Dowling, Sally; Oxford, Liz; Ellis, Nicola; Jones, Mat
ABSTRACT: Breastfeeding rates in the UK remain persistently low, with a rapid fall off during the first 6–8 weeks. The work of healthcare and public health practitioners impacts on mothers' experiences of infant feeding. Support, promotion and protection of breastfeeding are a national priority. Semi-structured qualitative interviews were undertaken with mothers who had experience of breastfeeding. Participants were engaged with a local Children's Centre (indicating engagement with public health provision) and their babies were up to 6-month old (to increase recall of early experiences). Twenty-four participants were recruited and interviews thematically analysed. Mothers identified matters significant in relation to public health provision for breastfeeding, including three stages of time of significance for breastfeeding impact. These interlinked critical stages impact on a mother's experiences. Joined up public health practice providing breastfeeding support and information before birth, around the time of the birth, and once home is significant in mother's accounts. Breastfeeding support, in both healthcare and public health contexts, needs to be highly attuned to different stages in the experiences of mothers. Breastfeeding continuation is influenced by support experienced antenatally, perinatally, and in early weeks. To enhance the initiation and retention of breastfeeding, public health practice must pay attention to these stages. Breastfeeding support needs to begin prior to birth and be given throughout the postnatal period and beyond.